Alveolar bone repair with strontium- containing nanostructured carbonated hydroxyapatite - André Boziki Xavier do Carmo; Suelen Cristina Sartoretto; Adriana Terezinha Neves Novellino Alves; José Mauro Granjeiro; Fúlvio Borges Miguel; Jose Calasans-Maia; Monica Diuana Calasans-Maia (University of São Paulo, 2018)
ABSTRACT Objective: This study aimed to evaluate bone repair in rat dental sockets after implanting nanostructured carbonated hydroxyapatite/sodium alginate (CHA) and nanostructured carbonated hydroxyapatite/sodium alginate containing 5% strontium microspheres (SrCHA) as bone substitute materials. Methods: Twenty male Wistar rats were randomly divided into two experimental groups: CHA and SrCHA (n=5/period/group). After one and 6 weeks of extraction of the right maxillary central incisor and biomaterial implantation, 5 μm bone blocks were obtained for histomorphometric evaluation. The parameters evaluated were remaining biomaterial, loose connective tissue and newly formed bone in a standard area. Statistical analysis was performed by Mann-Withney and and Wilcoxon tests at 95% level of significance. Results: The histomorphometric results showed that the microspheres showed similar fragmentation and bio-absorbation (p>0.05). We observed the formation of new bones in both groups during the same experimental periods; however, the new bone formation differed significantly between the weeks 1 and 6 (p=0.0039) in both groups. Conclusion: The CHA and SrCHA biomaterials were biocompatible, osteoconductive and bioabsorbable, indicating their great potential for clinical use as bone substitutes.